Alcance e apreensão de objetos em lactentes com síndrome de Down : impacto da interação organismoambiente - Campos, Ana Carolina de (Universidade Federal de São Carlos, 2009)
The acquisition and the refinement of motor skills have been described to require a reciprocal relationship between organismic and environmental conditions. This interaction is evidenced in studies identifying the impact of intrinsic and extrinsic factors on functional skills such as reaching and grasping objects. Thus, Study 1 was conducted in order to review the research on factors influencing reaching and grasping in infants at risk for developmental delays. The review has shown that few studies have aimed to understand the development of actions performed by Down syndrome (DS) infants, and also that there is a lack of information about these infants abilities to adjust their intrinsic properties to environmental demands. Consequently, two studies have been carried out. Study 2 aimed to describe the kinematic characteristics of reaching movements in 4-6-month-old DS infants and to test the influence of intrinsic factors, namely Down syndrome and gross motor skill level, on reaching and grasping behaviors. Seven infants with DS and seven infants with typical development (TD) were assessed at 4, 5 and 6 months-old. Gross motor skill was assessed by using Alberta Infant Motor Scale (AIMS). Infants were placed in a baby chair reclined 50º from the horizontal. A soft object (12.5 cm in diameter) was presented at infant s midline, shoulders height, and arm s length. The following variables were analyzed: straightness index (SI), mean velocity, movement units, deceleration time and grasping frequency. DS infants demonstrate variability in the age of reaching acquisition. The DS and the level of gross motor skills were found to influence grasping frequency. Faced with a task that did not impose excessive demand, kinematic characteristics of reaching in DS infants were quite similar to typical infants, except for the number of movement units at 5 months, which was higher for DS infants, and for SI at 6 months, which was lower for these infants. On the other hand, grasping frequency was lower for DS infants. In order to understand DS infants ability to reach for and grasp objects of different sizes, Study 3 was carried out. Grasping and kinematic characteristics of reaches performed by the same infants for large and small objects were analyzed. These reaches were recorded during the same experimental procedure of Study 2. The object size has induced kinematic changes in reaches performed by DS infants, what suggests that they are exploring strategies to move. The adoption of variable movement strategies suggests perception of affordances of the objects. Nevertheless, DS infants failed to grasp the object, which may indicate that they need more experience in the task in order to adapt their actions to their intrinsic constraints. The results of this study point to the importance of considering the individual variability and the confluence of multiple factors in the development of reaching and grasping, since the organismic conditions in interaction with the task demands, were found to influence reaching and grasping performance.
Reaching and grasping skills in Down syndrome infants: impact of organism-environment fit
Keywords: Lactentes; Desenvolvimento motor; Alcance manual; Apreensão; Propriedades dos objetos; Down, Síndrome de; Tamanho dos objetos; AIMS; Reaching; Grasping; Object size; Down syndrome; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL